2014
DOI: 10.1186/1471-2431-14-27
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dalteparin, a low-molecular-weight heparin, as adjunctive therapy in patients with Kawasaki disease: a retrospective study

Abstract: BackgroundDalteparin, a low-molecular-weight heparin, has anticoagulant and anti-angiogenic activity. This study investigated whether dalteparin reduced coronary artery lesion (CAL) prevalence, and resistance to intravenous immunoglobulin (IVIG) therapy in Kawasaki disease (KD).MethodsThis retrospective study comprised two parts. In the first cohort, 126 patients with KD (68 male, 58 female; median age: 22 months, range: 1–67 months) admitted to Nihon University Nerima-Hikarigaoka Hospital from January 2004 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 22 publications
0
5
0
1
Order By: Relevance
“…A recent study reported that 81% of patients with KD who eventually developed coronary aneurysms showed coronary abnormalities on their initial echocardiograms [ 12 ]. Studies have proposed the use of adjuvant therapies with agents such as atorvastatin [ 13 ], steroids [ 14 , 15 ], and dalteparin [ 16 ] to ameliorate the CALs of patients with KD during the acute KD phase. Friedman et al [ 17 ] demonstrated that the rate of coronary aneurysm regression was significantly higher in patients with KD receiving IVIG and adjunctive medications than in those not receiving such medications (91% vs 68%, P = 0.02).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported that 81% of patients with KD who eventually developed coronary aneurysms showed coronary abnormalities on their initial echocardiograms [ 12 ]. Studies have proposed the use of adjuvant therapies with agents such as atorvastatin [ 13 ], steroids [ 14 , 15 ], and dalteparin [ 16 ] to ameliorate the CALs of patients with KD during the acute KD phase. Friedman et al [ 17 ] demonstrated that the rate of coronary aneurysm regression was significantly higher in patients with KD receiving IVIG and adjunctive medications than in those not receiving such medications (91% vs 68%, P = 0.02).…”
Section: Discussionmentioning
confidence: 99%
“…reported the use of continuous intravenous infusion of dalteparin and oral aspirin with and without intravenous immunoglobulin (IVIG) in two retrospective cohorts of 238 Japanese children with Kawasaki's disease. They concluded that the antiangiogenic activity of adjunctive dalteparin was associated with a lower prevalence of coronary artery lesions and IVIG resistance .…”
Section: Introductionmentioning
confidence: 99%
“…They found a lower risk of coronary artery lesions within the first month (OR: 0.34; 95% CIL 0.17‐0.66) (low certainty of evidence) and decreased odds of needing additional treatment for refractory disease (OR: 0.48; 95% CI: 0.30‐0.76) (low certainty of evidence). There was no statistically significant difference in the odds of having a coronary artery lesion persist longer than 1 month when pooling their two cohorts (OR: 0.21; 95% CI: 0.04‐1.03) (low certainty of evidence) ( 47 ) (Tables 2 and 3 ).…”
Section: Resultsmentioning
confidence: 99%